2018
DOI: 10.17116/jnevro20181185139
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of neurotrophic therapy (a pilot study)

Abstract: The high clinical effect of neurotrophic therapy with cerebrolysin in MCI shows its anti-inflammatory and immunotropic action that suggests the impact of cerebrolysin on the pathogenesis of MCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…260 Recently, it was also found that Cerebrolysin normalized elevated levels of the proinflammatory c-reactive protein (CRP) in subjects with MCI, independently of its clinical effects. 227 These results are consistent with the previous observation of a significant increase in CRP levels over time and its lack of associations with cognition in MCI patients. 261 In AD patients of the dose-finding study, 217 Cerebrolysin enhanced serum concentrations of dissociable IGF-1 at doses of 10 and 60 ml, 162 and the levels of free IGF-1 with the 60 ml dosage.…”
Section: Effects Of Cerebrolysin On Neurotrophic and Inflammatory Markers In Ad And MCIsupporting
confidence: 93%
See 3 more Smart Citations
“…260 Recently, it was also found that Cerebrolysin normalized elevated levels of the proinflammatory c-reactive protein (CRP) in subjects with MCI, independently of its clinical effects. 227 These results are consistent with the previous observation of a significant increase in CRP levels over time and its lack of associations with cognition in MCI patients. 261 In AD patients of the dose-finding study, 217 Cerebrolysin enhanced serum concentrations of dissociable IGF-1 at doses of 10 and 60 ml, 162 and the levels of free IGF-1 with the 60 ml dosage.…”
Section: Effects Of Cerebrolysin On Neurotrophic and Inflammatory Markers In Ad And MCIsupporting
confidence: 93%
“…In participants of another AD clinical trial, 218 the combination therapy with Cerebrolysin and donepezil reduced serum TNF‐α levels significantly with respect to donepezil; and TNF‐α decreases correlated with improvements in ADL functioning and cognition at study endpoint (Week 28) 260 . Recently, it was also found that Cerebrolysin normalized elevated levels of the proinflammatory c‐reactive protein (CRP) in subjects with MCI, independently of its clinical effects 227 . These results are consistent with the previous observation of a significant increase in CRP levels over time and its lack of associations with cognition in MCI patients 261 …”
Section: Multitarget Neurotrophic Treatment With Cerebrolysin In Adsupporting
confidence: 82%
See 2 more Smart Citations
“…Cerebrolysin can penetrate the blood brain barrier (Akai et al, ; Bornstein et al, ; Muresanu et al, ; Stan, et al, ), improve functional cognitive outcomes in patients with dementia and traumatic brain injury, and improve neuro‐rehabilitation in patients with stroke (Gharagozli et al, ; Mahmoudi et al, ; Onose et al, ). More recently, there is evidence to suggest that cerebrolysin may also produce an anti‐inflammatory and analgesic effect (Dong et al, ; Mahmoudi et al, ; Malashenkova et al, ; Morales‐Medina, et al, ; Sharma et al, ). With the increasing evidence of the benefit of cerebrolysin in inflammation, we aim to build upon the findings of our previous study (Morales‐Medina et al, ) by investigating the response to acute administration of cerebrolysin in another model of peripheral inflammation and also assess sex differences.…”
Section: Introductionmentioning
confidence: 99%